2007
DOI: 10.1002/poc.1144
|View full text |Cite
|
Sign up to set email alerts
|

Structure and reactivity in the hydrolyses of aliphatic carboxylic acid esters and chlorides

Abstract: For hexanoic acid and its seven isomers, relative rates have been determined for acid catalysed esterification with methanol, and compared with those for saponification of the methyl esters. A good correlation between logarithms of relative rates for the two reactions is obtained, and it is suggested that the eight isomers provide a test set of compounds in which steric effects alone act on reactivity at the acyl carbon. A full set of steric parameters ($E_{\rm s}^\prime$ values) are presented. Rates of solvol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…It is to be noted, however, that acetyl chloride is not protonated in solvolyses under normal reaction conditions 48, 49. It has also been suggested that dissociation of the chloride ion may follow the hydration of acetyl chloride,23, 32, 33 though neither the fast10, 11 nor the slow14 prior formation of the hydrate was supported by experimental data 42…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…It is to be noted, however, that acetyl chloride is not protonated in solvolyses under normal reaction conditions 48, 49. It has also been suggested that dissociation of the chloride ion may follow the hydration of acetyl chloride,23, 32, 33 though neither the fast10, 11 nor the slow14 prior formation of the hydrate was supported by experimental data 42…”
Section: Resultsmentioning
confidence: 98%
“…The hydrolyses of acid chlorides were also supposed23, 32, 33 to proceed through the hydrated substrates, though these intermediates have neither been synthesized nor detected in the reaction mixtures. Acetyl chloride hydrate could be formed if the nucleophilic attack of water on the carbonyl group would be accompanied by a proton transfer towards the oxygen atom of the CO group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimates based on kinetic data at 0 °C show that acetyl chloride reacts about 5 orders of magnitude faster than predicted from Equation 3, and a prior hydration mechanism could not be excluded [24,37]. Recent extensive DFT calculations included a wide range of acid chlorides and optimized structures of assemblies including molecules of water and acetone.…”
Section: Resultsmentioning
confidence: 99%
“…Logarithms of relative rates for the acid-catalysed esterifications provide the traditional steric substituent parameters, E s , and we have tabulated those for the C 5 H 11 isomers in our earlier paper. [1] It is clear that relative rates for the ester saponifications might equally be used to compare steric demand within this series.…”
Section: Introductionmentioning
confidence: 99%